Electrically conducting polymer blends with thermally processable polyaniline - Choi, DU; Song, K; Kim, YC; Park, YH; Lee, JY (TAYLOR & FRANCIS LTD, 2001)
Thermally processable polyaniline (PANI) was synthesized by one-step chemical oxidation of aniline, whose electrical conductivity was in the range of 10(-2) to 1 S/CM. Various kinds of thermoplastic polymers were thermally blended with the processable PANI, giving rise to the electrically conducting polymer blends with the specific volume resistivity of 10(2) to 10(10) Ohm -cm.